2014
DOI: 10.4103/2230-8229.134766
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lifestyle modification on severity of constipation and quality of life of elders in nursing homes at Ismailia city, Egypt

Abstract: Background:Constipation has a significant impact on the quality of life (QOL). Lifestyle modification is widely accepted and recommended by experts as first-line therapy.Aim:This study aimed at using education on lifestyle modification to improve the QOL of the elderly in nursing homes suffering from functional constipation (FC).Materials and Methods:This study was conducted in nursing homes in Ismailia city, Egypt. It involved 23 elderly patients suffering from FC, who were randomly selected according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Improvement in the satisfaction subscale was also identified in a recent pre‐ to postintervention study intervening with three sessions of group‐based health education ( n = 23); the mean score changed from 5·3 (SD 1·7)–10·6 (SD 2·5) ( p < 0·001) (Nour‐Eldein et al . ). Marteau et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Improvement in the satisfaction subscale was also identified in a recent pre‐ to postintervention study intervening with three sessions of group‐based health education ( n = 23); the mean score changed from 5·3 (SD 1·7)–10·6 (SD 2·5) ( p < 0·001) (Nour‐Eldein et al . ). Marteau et al .…”
Section: Resultsmentioning
confidence: 97%
“…Only one pre‐ to postintervention study found significant improvement in the subscale of worries in PAC‐QOL after the intervention of group‐based intervention programme focusing on lifestyle modification in relation to constipation (14·4 (SD 11·8) vs. 6·7 (SD 6·1) ( p = 0·004)) (Nour‐Eldein et al . ). The subscale of worries included 11 questions about being worried or irritable about the condition, being afraid it might get worse and feeling less confident or not in control (Marquis et al .…”
Section: Resultsmentioning
confidence: 97%
“…'Treatment satisfaction', as factor or an item, is a common inclusion in many constipation-related scales (Li, Lee & Suen, 2014;Müller-lissner et al, 2010;Müller-Lissner et al, 2013;Nour-Eldein et al, 2014). Earlier QoL scales had a 'satisfaction' subscale, but items were heterogeneous and based on frequency and regularity in bowel movements, activities, expectations, values, effectiveness and treatment satisfaction (Marquis et al, 2005;Szeinbach et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] For that reason, we have a low recommendation for isolated changes in fiber intake, but a strong recommendation for a general intervention in the conjunction of lifestyle modifications, including dietary advice, physical exercise, and defecation habits. 4,5 In patients with constipation associated with irritable bowel syndrome, the increment in bowel contents, both water and gases, induced by fibers may be poorly tolerated by these patients, probably related to the visceral hypersensitivity that characterizes this disorder. 6 For that reason, the guideline recommends to use soluble fiber in these patients, and in patients with functional constipation who we strongly recommend this treatment modality.…”
Section: Responses To the Letter To The Editor By Brusciano Et Almentioning
confidence: 99%